IMPLEMENTASI KEBIJAKAN REVITALISASI KAWASAN CAGAR BUDAYA (STUDI PADA JALAN PANGGUNG KOTA LAMA, SURABAYA) - Dimas Adi Mahindra; Suci Megawati (Publika, 2022)
The existence of a cultural heritage area in the Old City of Surabaya is one of the advantages of the City of Surabaya and makes it an attraction for tourists. However, the rapid development experienced has made the Old City neglected which has an impact on the decline in the existence of the building. The Surabaya City Government already has Regional Regulation No. 5 of 2005. Surabaya Government the Department of Culture and Tourism seeks to preserve these buildings through revitalization. One of them is on Jalan Panggung which aims to deal with dull buildings and a lack of tourists. But in fact this revitalization raises problems in the form of rejection by some people because this revitalization is carried out with colorful painting which is considered not accordance with the architectural characteristics of old buildings and eliminates the historical value that exists in the Jalan Panggung area. The purpose of this study is to describe the implementation of the revitalization policy of the cultural heritage area on Jalan Panggung Kota Lama, Surabaya. Research method uses a descriptive qualitative approach, the data collection methods are observation, documentation, and interviews. Results of this study are the policy is optimal in preserving cultural heritage, the accuracy of the implementation is less than optimal from a technical point of view because there is no agreement with historical activists, the accuracy of the target is not optimal, because some parties who intervened showed disagreement, environmental accuracy is not optimal because there are perceptions of institutions strategic, namely the community of historical activists. Suggestions given are maturation of short and long term plans, increasing coordination between government and non-government parties, holding discussion forums with related parties, actively involving the community in preserving heritage. Keywords: Policy Implementation, Revitalization, Cultural Heritage Areas.